A Brief Analysis of Equivalence Demonstration Techniques for Clinical Evaluation of Medical Devices - Tian, Huanhuan; Wu, Sujing; Liang, Yu; Wang, Weili; Ji, Chengxue (Zhongguo yi liao qi xie za zhi, 2023)
This study overviewed equivalence demonstration, the principles for the selection of comparative devices, the difficulties in equivalence demonstration, and the equivalence demonstration of special medical devices. In addition, the concept of equivalence demonstration was adopted for the products exempted from clinical evaluation, and there were many confusion in actual use. The operation points and difficult points of equivalence demonstration for the products exempted from clinical evaluation were introduced in order to provide reference for medical device colleagues.